LES FILMS "PERDUS" DE LA GUERRE OUBLIÉE - LACASSE, GERMAIN (Revue Canadienne d'Études cinématographiques / Canadian Journal of Film Studies, 1998)
This article provides a brief history and description of films depicting Canadian participation in World War I and a report on their current status as archival documents. Noting plants to sell some of this irreplaceable footage as stock shots, the author makes a strong plea for the preservation and thorough cataloguing of all documentary footage from that extremely significant period in the history of Canada and Québec.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS8yNDQwMjM0NQ